Banking geography and cross-fertilization in the productivity growth of US commercial banks - Dogan Tirtiroglu; A. Basak Tanyeri; Ercan Tirtiroglu; Kenneth N. Daniels (Koç University-TÜSİAD Economic Research Forum (ERF), 2011)
The US banking industry offers a unique, natural and fertile environment to study geography's effects on banks' behavior and performance. The literature on banks' operating performance, while extensive, says little about the influence of spatial interactions on banks' performance. We compute and examine, using a physical distance-based spatio-temporal empirical model, the state-wide total factor productivity growth (TFPG) indices of US commercial banks for each state for the 1971-1995 period. We observe that the productivity growth of commercial banks in state i depends strongly, positively, and contemporaneously on the productivity growth of commercial banks located in state i's contiguous states. Further, regulatory space appears to induce frictions and lessen the documented spatial interactions. These findings support our plea that research on commercial banking sector's behavior need to pay a particular attention to the effects of banking geography.
Keywords: D24; C23; G21; G28; K23; 330; Spatial; Commercial Banks; Total Factor Productivity Growth; Kalman Filter; Bankgeschäft; Produktivität; Räumliche Verteilung; Teilstaat; Zustandsraummodell; Schätzung; USA